COMPARISON OF PERFORMANCE CHARACTERISTICS OF GAMMA CAMERAS WITH SCINTILLATION NaI (TI) AND SEMICONDUCTOR CdZnTe DETECTORS. - AYDIN, Armağan; ÇETİN, Füsun; DEMİR, Mustafa (Journal of Advanced Research in Health Sciences (JARHS) / Sağlık Bilimlerinde İleri Araştırmalar Dergisi (SABİAD), 2024)
Objective: In recent years, gamma cameras with semiconductor detectors (CdZnTe) have entered routine practise diagnostic scintigraphic imaging in nuclear medicine. In this study, we aimed to compare the performance characteristics of a gamma camera with a semiconductor detector (CdZnTe) and a conventional gamma camera with a NaI(Tl) detector. Material and Methods: In our experimental studies, spatial resolution, energy resolution, and linearity tests were performed using 3 capillary tubes of the same length and thickness, into which the Tc-99m radioisotope with different activities was placed. Sensitivity tests were performed by placing Tc-99m in a plastic Petri dish with a diameter of 3 cm. Scintigraphic images of the capillary tubes and the Petri dish were taken with both gamma cameras under equal geometric conditions. Regions of interest (ROI) were drawn on the images. The activity amount corresponding to the counts in the ROI was determined. Results: The spatial resolution, energy resolution, and sensitivity values of the gamma camera with the CdZnTe detector and the gamma camera with NaI(Tl) detector are respectively: 7.16 mm, 5.1% and 17.5 cps/µCi for CdZnTe, and 13.2 mm, 9.4% and 3.9 cps/µCi for NaI(Tl) µCi respectively. Conclusion: According to the results of our study, it was concluded that the energy resolution, spatial resolution, sensitivity, and linearity properties of the gamma camera with the semiconductor CdZnTe detector are superior to those of the gamma camera with the NaI(Tl) detector.